Cesarean delivery on maternal request and its influencing factors in Chongqing, China - Ruibin Deng; Xian Tang; Jiaxiu Liu; Yuwen Gao; Xiaoni Zhong (BMC, 2021)
Abstract Background A high rate of cesarean delivery has become a cause of global concern. Although the rate of cesarean delivery has declined over recent years, it remains at a high level largely because of cesarean delivery on maternal request (CDMR). Unnecessary cesarean delivery has limited significance in benefiting maternal and infant physical health; in some ways, it might pose potential risks instead. With the implementation of the "Two-child Policy" in China, an increasing number of women plan to have a second child. Accordingly, how to handle the CDMR rate in China remains an important issue. Methods Data were collected from a longitudinal follow-up study conducted in Chongqing, China, from 2018 to 2019. A structured questionnaire was administered to subjects for data collection. Basic information, including demographic characteristics, living habits, medical history, and follow-up data of pregnant women, as well as their families and society, was collected. Additionally, delivery outcomes were recorded. Logistic regression was performed to analyze the factors influencing CDMR. Results The rate of cesarean delivery in Chongqing, China was 36.01 %, and the CDMR rate was 8.42 %. Maternal request (23.38 %), fetal distress (22.73 %), and pregnancy complications (9.96 %) were the top three indications for cesarean delivery. Logistic regression analysis showed that older age (OR = 4.292, 95 % CI: 1.984-9.283) and being a primiparous woman (OR = 6.792, 95 % CI: 3.230-14.281) were risk factors for CDMR. In addition, CDMR was also associated with factors such as the tendency to choose cesarean delivery during late pregnancy (OR = 5.525, 95 % CI: 2.116-14.431), frequent contact with mothers who had undergone vaginal deliveries (OR = 0.547, 95 % CI: 0.311-0.961), and the recommendation of cesarean delivery by doctors (OR = 4.071, 95 % CI: 1.007-16.455). Conclusions "Maternal request" has become the primary indication for cesarean delivery. The occurrence of CDMR is related to both the personal factors of women during pregnancy and others. Medical institutions and obstetricians should continue popularizing delivery knowledge among pregnant women, enhancing their own professional knowledge about delivery, adhering to the standard indications for cesarean delivery, and providing pregnant women with adequate opportunities for attempting vaginal delivery.